A review of the leafhopper genus Scaphytopius (Cicadellidae: Deltocephalinae) from Costa Rica with descriptions of sixteen new species - Arias-Paco, Andrés; Godoy, Carolina (Zootaxa, 2025)
The genus Scaphytopius is a group of leafhoppers widely distributed in the Americas with phytoplasma vector species. A possible vector of phytoplasmas has been found in Costa Rica, but the taxonomy of the group has been little studied in Central America. Therefore, the aim of this study was to review the taxonomy of the genus in Costa Rica, based on the main entomological collections of the country. We found sixteen new species, and nine species that are new records for the country. We also provide a key for the identification of the twenty-nine species present in Costa Rica.